2007
DOI: 10.1161/01.atv.0000253889.09765.5f
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Spectrometric Identification of a Novel Angiotensin Peptide in Human Plasma

Abstract: Objective-Angiotensin peptides play a central role in cardiovascular physiology and pathology. Among these peptides, angiotensin II (Ang II) has been investigated most intensively. However, further angiotensin peptides such as Ang 1-7, Ang III, and Ang IV also contribute to vascular regulation, and may elicit additional, different, or even opposite effects to Ang II. Here, we describe a novel Ang II-related, strong vasoconstrictive substance in plasma from healthy humans and end-stage renal failure patients. ]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
185
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(197 citation statements)
references
References 26 publications
4
185
1
7
Order By: Relevance
“…8 In the presence of mononuclear leukocytes, Ang A appears to be generated from Ang II by enzymatic decarboxylation of Asp 1 (ref. 8).…”
Section: Angiotensin II At 1 and At 2 Receptorsmentioning
confidence: 99%
See 4 more Smart Citations
“…8 In the presence of mononuclear leukocytes, Ang A appears to be generated from Ang II by enzymatic decarboxylation of Asp 1 (ref. 8).…”
Section: Angiotensin II At 1 and At 2 Receptorsmentioning
confidence: 99%
“…8). Jankowski et al 8 claimed that Ang A is a partial agonist with the same affinity for the AT 1 receptor as Ang II, but a higher affinity for the AT 2 receptor (Figure 2). More recent in vitro binding studies of Ang A in CHO-hAT 1 and to CHO-AT 2 cells did not confirm this, and showed that Ang A has similar binding affinity for the AT 1 receptors and the AT 2 receptors as Ang II.…”
Section: Angiotensin II At 1 and At 2 Receptorsmentioning
confidence: 99%
See 3 more Smart Citations